2022
DOI: 10.1371/journal.pone.0265826
|View full text |Cite
|
Sign up to set email alerts
|

Mapping local hot spots with routine tuberculosis data: A pragmatic approach to identify spatial variability

Abstract: Objective To use routinely collected data, with the addition of geographic information and census data, to identify local hot spots of rates of reported tuberculosis cases. Design Residential locations of tuberculosis cases identified from eight public health facilities in Lima, Peru (2013–2018) were linked to census data to calculate neighborhood-level annual case rates. Heat maps of tuberculosis case rates by neighborhood were created. Local indicators of spatial autocorrelation, Moran’s I, were used to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The study found that while the median rate of reported cases in the district was 123.6, the range among neighbourhoods varied from 0 to 800 cases per 100,000 population. While the study utilised notification registers alone, it highlights the possibility of local epidemics and relevance of geographic mapping of individual cases from their addresses to identify areas at risk of TB transmission and its practical implications for decision making [31].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that while the median rate of reported cases in the district was 123.6, the range among neighbourhoods varied from 0 to 800 cases per 100,000 population. While the study utilised notification registers alone, it highlights the possibility of local epidemics and relevance of geographic mapping of individual cases from their addresses to identify areas at risk of TB transmission and its practical implications for decision making [31].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that while the median rate of reported cases in the district was 123.6, the range among neighbourhoods varied from 0 to 800 cases per 100,000 population. While the study utilised notification registers alone, it highlights the possibility of local epidemics and relevance of geographic mapping of individual cases from their addresses to identify areas at risk of TB transmission and its practical implications for decision making [35].…”
Section: Discussionmentioning
confidence: 99%
“…This understanding can help inform public health actions, such as the customization and targeting of interventions (9). Finer spatial resolution of TB data is required in order to create successful interventions for local zones; this means moving away from solely examining nationally aggregated data and toward using pertinent local data (10). The better utilization of already-existing data, such as program reports of tuberculosis cases, and the extension of that routine data to incorporate spatial information are crucial to this change (9).…”
Section: Introductionmentioning
confidence: 99%